Creating Reflective Space for Reflective and "Unreflective" Medical Students: Exploring Seminal Moments in a Large-Group Writing Session. (June 2020) - Campbell, Bruce H.; Treat, Robert; Johnson, Benjamin; Derse, Arthur R.
Abstract : Problem: Reflection is a critical skill for all physicians, but some busy medical students describe themselves as "unreflective." The authors sought to provide all third-year medical students at the Medical College of Wisconsin (MCW) with opportunities to explore seminal clinical and personal moments through reflective writing during workshops on preparing a personal statement for the Electronic Residency Application Service. Approach: The authors developed and facilitated semiannual 1.5- to 2-hour sessions (January and June) for MCW third-year medical students (about 200 per class), pairing information on personal statements with reflective writing and group reflection activities. Students wrote reflectively but were not required to share their writing with peers or faculty. They discussed insights gleaned during the writing process in small groups and with the class. They completed pre- and postsession questions on an anonymous questionnaire. Outcomes: Eight all-class sessions were held between January 2015 and June 2018. Students completed 1, 139 of 1, 600 questionnaires (completion rate of approximately 71%). They misperceived their peers' views of reflective activities. Twice as many students agreed their peers felt writing, reflective, and narrative exercises were a waste of time as they themselves did (39% vs 19%). While 42% entered the session comfortable with creative writing, 57% were surprised by the amount, quality, and/or insight of their writing during the session and 77% agreed the session helped them think more clearly about clinical encounters. Students who believed reflective writing was a waste of time were more likely to believe their peers felt that also, and they were less likely to believe the session helped them reflect on clinical experiences. Most written comments were positive. Next Steps: To expose students to narrative medicine techniques, the authors added a close-reading exercise and shortened the reflective writing activity in 2019, hoping this would better equip all students for their journeys. Abstract : Supplemental Digital Content is available in the text.